Who Should Have a Place on the Ark? Parameterized algorithms for the maximization of the Phylogenetic Diversity - Schestag, Jannik (2025)
First and foremost, I humbly thank my redeemer, Jesus Christ, through whom the foundations of the heavens and the earth were created (Colossians 1:16, John 1:3) and who died on the cross as I deserve (Romans 6:23) so that I may live as He deserves (2 Corinthians 5:21). Jesus not only became my God but also my best friend. All the strength, concentration, and willpower I needed to accomplish every part of this work were surely given by Him (Philippians 2:13). All glory, honor, and power be unto Him forever and ever (Revelation 4:11). Amen! Academically, I express my deepest gratitude to my supervisor, Christian Komusiewicz, for his multitude of great ideas and quick answers to my questions. Additionally, I thank him for the endless hours spent writing applications and for always staying supportive, even in situations where many other professors would have opted out. Though officially he is just a co-author, I want to thank Mark Jones as a ‘minor’ supervisor. His knowledge, humor, and way of working during the cooperative time left a very positive feeling with me and deőnitively improved my working spirit. Furthermore, I am grateful to Niels Grüttemeier and Frank Sommer, who initially supervised my Bachelor’s and Master’s degrees and later became colleagues. Also, I thank my other colleagues Alexander Bille, Jaroslav Garvardt, Nils Morawietz, Luca Staus, and the Master’s student Anton Herrmann, for creating a pleasant working atmosphere, sharing one or the other joke in times, and providing deep talks. I further want to thank all of my co-authors, listed in lexicographic order: Matthias Bentert, Jaroslav Garvardt, Niels Grüttemeier, Leo van Iersel, Mark Jones, Christian Komusiewicz, Simone Linz, Ber Lorke, Nils Morawietz, Malte Renken, Frank Sommer, Celine Scornavacca, and Mathias Weller. Gratefully, I received a őnancial support by the Deutscher Akademischer Austauschdienst (DAADÐGerman Academic Exchange Service), project 57556279, from April to September 2023. I thank the TU Delft and especially Leo van Iersel, Mark Jones, and their colleagues for hosting me during this period. Last but not least, for their unwavering support throughout my life, I want to express my sincerest thanks to my mother, Kerstin Schestag, and my sister, Mona Felina Schestag. Surely, I would have not come to where I am without them. While it is impossible to list all the important people in my life, I explicitly want to express thanks to my grandmother Edeltraud Schestag, Klaus Pieper, Holger & Regine Hellmich, Ricarda Schwarz, the Slembeck family, the Köhler family, Niklas Vogt, Jan Mischon, my late father Joachim Schestag, my late grandfather Ulrich Hellmich, and everyone who supportively prayed for me!